Being sensitive in their own way: parental ethnotheories of caregiver sensitivity and child emotion regulation across five countries - Song, Ju-Hyun; Cho, Sook In; Trommsdorff, Gisela; Cole, Pamela; Niraula, Shanta; Mishra, Ramesh (Frontiers in Psychology, 2023)
Caregiver sensitivity builds a basis for children’s sense of security and effective emotion regulation during their development. Applying a cross-cultural lens, caregiver sensitivity can be divided into two subtypes, reactive and proactive, and its prevalence and meaning may differ across cultures. Guided by the theoretical frameworks of developmental niche and parental ethnotheories, the current study examines culture-specific meanings of caregiver sensitivity across five countries: India, Nepal, Korea, the United States of America (USA), and Germany. We examine the prevalence of maternal reactive and proactive sensitivity, children’s emotional lability and regulation, and how mothers’ sensitivity types are related to children’s emotional characteristics. Participants included 472 mothers from the five countries with children aged between 6 and 7 years. Mothers reported their sensitivity preference in multiple vignettes and completed an emotion regulation checklist to report their children’s emotional lability and regulation. A set of analyses of covariance (ANCOVAs) found cultural differences in mothers’ preference for proactive and reactive sensitivity. Mothers in India and Nepal reported the highest preference for proactive sensitivity followed by Korea and the USA, while German mothers reported the lowest preference for proactive sensitivity. Consequent regression analyses revealed varying associations between proactive sensitivity and child emotional characteristics in all five countries either directly or as moderated by child sex. These results evidence that parental ethnotheories are part of the developmental niche embedded in a larger cultural context. Findings on the differential links between the types of sensitivity and child emotion regulation provide cultural models of parental emotion socialization and children’s emotional functioning.